Intervention Service in Situations of Trafficking, Migration, Repatriation, Street Exploitation and the Role of the Social Worker - Grigore, Marinela Carmen; Stănescu, Nina; Popescu, George Sorin (Technium Social Sciences Journal, 2023)
The importance and the essential role of the social worker who works in the Intervention Service in Situations of Trafficking, Migration, Repatriation, Exploitation and Street Assistance are highlighted in this article. The protection and promotion of children's rights in Romania is carried out both at local level in communities, but mainly through specialised services in each county of the country. Assessing the role of the social worker, a member of the multidisciplinary team, in the context of protection and promotion of children's rights in situations of trafficking, migration or repatriation, it is possible to understand the complexity of his/her work in coordinating specialised interventions. The social worker is present with the beneficiaries in order to provide social services according to their needs, and when the recipients of these services are children, the social worker has the main role in accompanying the child and the family throughout this process, showing empathy and compassion towards them.